Oracle automatic storage management : - Vengurlekar, Nitin. (Oracle Press/McGraw-Hill, 2008)
Streamline data management and provisioning using Oracle Automatic Storage Management (Oracle ASM) and the detailed information contained in this exclusive Oracle Press resource. Written by a team of database experts, Oracle Automatic Storage Management: Under-the-Hood & Practical Deployment Guide explains how to build and maintain a dynamic, highly available Oracle database storage environment. Inside, you'll learn how to configure storage for Oracle ASM, build disk groups, use data striping and mirroring, and optimize performance. You'll also learn how to ensure consistency across server and storage platforms, maximize data redundancy, and administer Oracle ASM from the command line.